ISLAM, MINORITAS DAN PLURALISME DI INDONESIA - Moh Hasim (Analisa: Journal of Social Science and Religion, 2008)
Because of governmental system that acknowledged six officialreligions (Islam, Christian, Catholic, Hindu, Buddha, and Confucius),Indonesia as democratic country are judged by international worlddoing religious discrimination on other religious minority group(outside official religion). The role of MUI as authoritative religiousagency, exactly, worsen religious belief conflicts by giving label"deviant" on new religious/stream/belief out of mainstream officialreligions. Hegemony interests of religious majority groups(organizations) as moral power that has the right to claim about thetruth in governmental system has jeopardize pluralism structures inIndonesia. Pluralism by MUI is forbidden with the reason of insultingreligious truths. While Islam as major religion follow by Indonesiancommunity has explained that pluralism is a reality that becomenatural law and could not be denied.